Analysis of interaction between the apicomplexan protozoan Toxoplasma gondii and host cells using label-free Raman spectroscopy. Issue 3 (25th November 2014) - Naemat, Abida; Elsheikha, Hany M.; Al-sandaqchi, Alaa; Kong, Kenny; Ghita, Adrian; Notingher, Ioan
Abstract : Raman micro-spectroscopy was used to characterize time- and spatially-dependent molecular interactions between intracellular pathogens and the host cells. Abstract : Label-free imaging using Raman micro-spectroscopy (RMS) was used to characterize the spatio-temporal molecular changes of T. gondii tachyzoites and their host cell microenvironment. Raman spectral maps were recorded from isolated T. gondii tachyzoites and T. gondii -infected human retinal cells at 6 h, 24 h and 48 h post-infection. Principal component analysis (PCA) of the Raman spectra of paraformaldehyde-fixed infected cells indicated a significant increase in the amount of lipids and proteins in the T. gondii tachyzoites as the infection progresses within host cells. These results were confirmed by experiments carried out on live T. gondii -infected cells and were correlated with an increase in the concentration of proteins and lipids required for the replication of this intracellular pathogen. These findings demonstrate the potential of RMS to characterize time- and spatially-dependent molecular interactions between intracellular pathogens and the host cells. Such information may be useful for discovery of pharmacological targets or screening compounds with potential neuro-protective activity for eminent effects of changes in brain infection control practices.